HPV-specific antibodies at the oral cavity up to 30 months after the start of vaccination with the quadrivalent HPV vaccine among mid-adult aged men. Issue 21 (9th May 2019) - Parker, Katherine H.; Kemp, Troy J.; Isaacs-Soriano, Kimberly; Abrahamsen, Martha; Pan, Yuanji; Lazcano-Ponce, Eduardo; Salmeron, Jorge; Pinto, Ligia A.; Giuliano, Anna R.
Abstract: Background: HPV-16 and HPV-18 cause most oropharyngeal cancers, which are increasing in incidence among males. Although HPV vaccines are highly effective against a number of HPV-associated cancers, efficacy for oropharyngeal cancers has not yet been demonstrated. In addition, the level of antibodies required for protection against oral HPV infection is unknown. Methods: 150 men ages 27–45 years from Tampa, FL, USA, and Cuernavaca, Mexico, received Gardasil at Day 1, Months 2, and 6. Then, sera and oral gargles were collected one month, 12 months, and 24 months after completion of the three doses (Month 7, 18 and 30 of the study) and tested for anti-HPV-16 and HPV-18 IgG antibody levels by a L1 VLP ELISA. Results: All participants developed detectable serum anti-HPV-16 and anti-HPV-18 antibodies and most had detectable antibodies in oral gargles at Month 7 (HPV-16: 93.2%; HPV-18: 72.1%). By months 18 and 30, oral antibodies were detectable in a lower number of participants (HPV-16, 39.8% and 29.6%; HPV-18, 10.7% and 4.6% of individuals, respectively). Overall, oral HPV-16- and 18-specific antibody levels, normalized to total IgG at months 7, 18, and 30, correlated with serum levels (HPV-16, R 2 = 0.93; HPV-18, R 2 = 0.91). Conclusions: Reduced detectability of oral and serum HPV-16 and HPV-18 antibodies was observed at months 18 and 30 after initiation of the quadrivalent vaccination. However, when detectable, serum and oral HPV-16 and HPV-18 antibody levels were strongly correlated.